2020
DOI: 10.20319/pijss.2020.61.533544
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Reading Comprehension Skill: The Roles of Text Readability and Question Difficulty

Abstract: This research is trying to investigate whether students' difficulties in comprehending high-order questions are related to the readability of the reading text and the difficulty of the questions. The subjects in this research are freshmen in Institut Teknologi Kalimantan. Using random sampling, students with different levels of reading skills are chosen. This research asked students to answer reading comprehension tests, consisting of questions ranging from literal to evaluative questions, with reading texts r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…As mentioned above, there are few studies on the influence of text readability on students' reading comprehension. Despite the few relevant studies, this finding confirms the results of the study by Dirgantari and Susantiningdyah [30] that there is a significant relationship between the readability and comprehension of texts. While their study did not cover the trend of the correlation or the effects, we now have a clear picture: the higher the FKGL score, the lower the readability and the more difficult the text.…”
Section: Text Readability and Students' Reading Comprehensionsupporting
confidence: 88%
See 1 more Smart Citation
“…As mentioned above, there are few studies on the influence of text readability on students' reading comprehension. Despite the few relevant studies, this finding confirms the results of the study by Dirgantari and Susantiningdyah [30] that there is a significant relationship between the readability and comprehension of texts. While their study did not cover the trend of the correlation or the effects, we now have a clear picture: the higher the FKGL score, the lower the readability and the more difficult the text.…”
Section: Text Readability and Students' Reading Comprehensionsupporting
confidence: 88%
“…Several studies have been conducted focusing on matching the readability level of reading materials to the language proficiency levels of intended readers [26]- [28], text readability and readers' perceived readability [29], and the interaction between text readability and the level of task difficulty [22]. We found only one study, which was slightly related to the aim of this study, but the study was more focused on assessing the relationship between students' challenge in understanding inference text-based questions and the readability of the reading text [30]. The study concluded that there is a significant relationship between the readability of the text, the difficulty of the questions and the students' understanding.…”
Section: Introductionmentioning
confidence: 93%
“…As a textual complexity dimension, text readability has been one of the text characteristics that inform the legibility level of a reading text [ 39 , 40 ]. Several literatures have addressed issues regarding textual complexity.…”
Section: Theoretical Backgroundmentioning
confidence: 99%